THE ROLE OF LABOR CAPITAL AND MARKETING IN EFFORTS TO INCREASE THE INCOME OF SALT FARMERS IN GAMPONG TANOH ANOE, TERM DISTRICT, BIREUEN DISTRICT - Iskandar Iskandar; Jamaluddin Jamaluddin (Jurnal Ekonomi, 2023)
This research is motivated by the low income of salt farmers so far, especially in Gampong Tanoh Anoe, Jangka District, Bireuen Regency. The study aims to determine the role of capital, labor, and marketing in increasing salt farmers' income in Gampong Tanoeh Anoe, Jangka District, Bireuen Regency. The approach used in this research is qualitative. This type of research uses descriptive qualitative. The subjects in this study were ten salt farmers. Data collection techniques using observation, interviews, and documentation. Data analysis techniques include data reduction, presentation, and conclusion and verification. The study results show that capital is essential in increasing salt farmers' income in Gampong Tanoh Anoe, Jangka District, Bireuen Regency. The greater the money issued, the better the farmers' income; this business influences capital. Labor in this business is not very important for the payment of salt farmers in Gampong Tanoh Anoe, Jangka District, Bireuen Regency. This is based on the fact that labor is only used during the packaging process, nothing else. Marketing/promotion plays a significant role in advancing the business of salt farmers in Gampong Tanoh Anoe, Jangka District, Bireuen Regency. This is based on the quality and location that farmers will market during salt production.